Pilot Study on Development of Mobile Water Treatment System for Flood Prone Area - Theeba, M. Rajasegran; Easther, George Kiluk; Toh, Wei Kian; Foo, Qiao Lin; Lee, Pui Chee; Singh, Lakhveer (Penerbit Universiti Malaysia Pahang, 2015)
Supplying clean drinking water to the flood victim is the major problem during the flood seas on due to the heavy weight of the water which makes it hard for supplying enough clean drinking water to the victims. In this project, we develop a mobile water system for flood prone area which is called Ultra Micro Bamboo Filter (UMBF). The flow rate of this system is 5.56mL/s and the system have weight of 14kg and dimension of 42cm length, 82cm height and 28cm width. Ultra Micro Bamboo Filter (UMBF) was designed to be mobile and to filter out flood water to drink able water for flood victims. The UMBF consist of 5 parts which are fabricated into an arrangement of sand filter, ceramic filter, activated carbon, hollow fiber and the UV. Each of the parts was screwed to an aluminum which has been shaped to fit to a bag and pipes were used to connect all the parts so that water flows from one to another. Every parts have their own function where the sand filter were used to removes suspended particles such as leaves, twigs, or large, NanoAg + Carbon block are used to remove sediment, improve taste and odor reduction, the ceramic filter and hollow fiber were used to filter out the dangerous bacteri a and pathogen, and the UV is used to kill pathogen ic bacteria. In this project, water was collected from the drain besides Block T in Universiti Malaysia Pahang. The water was then poured directly into the first part where it flows throughout the UMBF according to the arrangements of the parts. The results of this project shows that the bacteria such as E.Coli and total Coliform were absent after the water were treated. Furthermore, the total suspended solid reduce from 42 mg/L to 1 mg/L, Nitrate-nitrogen was reduce from 13 .4mg/L to 8.1 mg/L, the color, iron and zinc were not detected which was from 25HU, 0.27 mg/L, and 0.0001 1mg/L after the water was treated with UMBF. All the parameter tested complies with the drinking Water standard asset by Ministry of Health Malaysia.